2021
DOI: 10.1158/1078-0432.ccr-20-4856
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Graft-versus-Host Disease on Survival in Acute Leukemia according to Donor Type

Abstract: Purpose: The anti-leukemic activity of allogeneic hematopoietic cell transplantation (HCT) depends on both the intensity of conditioning regimen and the strength of the graft-versus-leukemia (GVL) effect. However, it is unclear whether the sensitivity of the GVL effects differs between donor type and graft source. Experimental Design: We retrospectively evaluated the effect of acute and chronic graft-versus-host disease (GVHD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Furthermore, although the proportion of patients with adverse cytogenetics increased over time throughout all cohorts, relapse-related mortality was significantly improved in the recent time period in patients with advanced phase at CBT but was not improved in patients with early phase at CBT. Although a reduction in the risk of relapse could depend on both the intensity of conditioning regimen [ 28 , 29 ] and the strength of the graft-versus-leukemia (GVL) effect [ 30 , 31 ], an improvement of relapse-related mortality over time is not entirely clear in patients with advanced phase at CBT. This is likely due to a significantly increased MAC regimen rather than enhanced a GVL effect because there was a progressive increase in MAC regimens over the three time periods among patients with advanced phase at CBT, but the incidences of acute and chronic GVHD did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the proportion of patients with adverse cytogenetics increased over time throughout all cohorts, relapse-related mortality was significantly improved in the recent time period in patients with advanced phase at CBT but was not improved in patients with early phase at CBT. Although a reduction in the risk of relapse could depend on both the intensity of conditioning regimen [ 28 , 29 ] and the strength of the graft-versus-leukemia (GVL) effect [ 30 , 31 ], an improvement of relapse-related mortality over time is not entirely clear in patients with advanced phase at CBT. This is likely due to a significantly increased MAC regimen rather than enhanced a GVL effect because there was a progressive increase in MAC regimens over the three time periods among patients with advanced phase at CBT, but the incidences of acute and chronic GVHD did not change.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect of excess of acute GVHD might be different between donor type. In fact, our previous studies showed that the development of mild acute GVHD improved survival only after UCB transplants, but these effects were not shown in patients receiving MSD and MUD transplants 45,46 . Furthermore, previous study demonstrated that a significantly higher response rate to systemic corticosteroids for grade II‐IV acute GVHD in UCB transplants compared with adult donor HCT 47 .…”
Section: Discussionmentioning
confidence: 98%
“…In fact, our previous studies showed that the development of mild acute GVHD improved survival only after UCB transplants, but these effects were not shown in patients receiving MSD and MUD transplants. 45,46 Furthermore, previous study demonstrated that a significantly higher response rate to systemic corticosteroids for grade II-IV acute GVHD in UCB transplants compared with adult donor HCT. 47 These data suggest that intensified conditioning regimen could contribute to the stronger GVL effects after UCB transplants, whereas it could contribute to increasing NRM after MSD and MUD transplants.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed a different magnitude of GVL effect according to donor type; the GVL effect after CBT was more potent than that after BMT or PBSCT. 6 On the other hand, it can be assumed that the GVL effect after haplo-HSCT may not be so strong owing to the use of post-transplant cyclophosphamide or antithymocyte globulin. 7 Taken together, it is tempting to consider that optimal donor selection may depend on conditioning intensity, and CBT may be preferable to haplo-HSCT when MAC is chosen.…”
Section: Cord Blood Versus Haploidentical Transplantations For Non-re...mentioning
confidence: 99%